Penggunaan Media Alternatif pada Kultur In Vitro Jahe (Zingiber officinale Rosc.) Varietas Gajah - Ismiyati Sutarto; Nana Supriatna; , Yuliasti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
The problem faced in cultivation of ginger is the availability of uniform plant propagation materials.  Ginger is propagated through underground rhizomes. Growth of the  rhizome is not uniform, since the shoots do not sprout at the same time. Most of the rhizomes were attacked by several diseases such as bacterial wilt, soft rot, and nematodes. Propagation of plant material through in-vitro culture is also an obstacle since the price of pure agar and chemicals is very expensive. Therefore, production of cheap, uniform and disease-free plant materials with rapid multiplication rate is necessary for the successful ginger cultivation. The use of alternative media on in-vitro culture of ginger (Zingiber officinale Rosc.) cv. Gajah was conducted in order to substitute cheaper alternative media for in-vitro culture of ginger. An experiment using two basic composition of media (MS and liquid fertilizer) and three different types of agar (seaweed, Swallow and Oxoid agar) was done at the Tissue Culture Laboratory of Center for Research and Development of Isotope and Radiation Technology, Jakarta. The result showed that the highest shoot height, number of shoot and leaf was obtained from medium composition of sea weed and MS. Whilst the medium of Oxoid agar and MS produced the longest and the highest number of root. The cheapest medium was found from seaweed and liquid fertilizer composition, whereas the most expensive medium was from Oxoid agar and MS composition. Seaweed and Swallow agar in MS media showed similar growth performance as well as Oxoid agar in development of ginger plantlets.    Key words : Media, In-Vitro, Ginger